PENGARUH LIABILITAS TERHADAP PENGHASILAN BERSIH PADA BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN 2013-2017 - Indrawan, Bisma; Triaelsa Agustien, Widiani (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2019)
The purpose of this research is to analyze the influence of liability on net income at Badan Penyelenggaraan Jaminan Sosial (BPJS) Ketenagakerjaan period of 2013-2017. The method for this research used quantitative method, collected data by literature study, field study, and review of literature that relevance to the subject. While for data analysis using coefficient pearson product moment, coefficient of determination and linear regression analysis. The conducted of research, the influence of liabilities with net income and after measured correlation is 0,928 which mean very strong. Based on data analysis, a regression estimation model is formed Y = 599195049263,286 + 0,130X that every liability increasingly, it will be followed by increase in net income by Rp 130,- at a constant 599195049263,286. The amount of liability relationship to net income based on the coefficient of determination is 86,20% which means 13,80% influenced by other factor. The company have to solve: 1) increase in tax payable; 2) the amount of accrual expenses that causes an increase in the value of liabilities. The advice given in this study are: 1) pay attention to expense that can trigger the increase in the value of liabilities; 2) re-establish the fair value of available investment assets.